Practice and the human sciences : the case for a judgment-based practice of care - Polkinghorne, Donald, 1936- (Albany : State University of New York Press, 2004)
"Teachers, nurses, psychotherapists, and other practitioners of care are under pressure to substitute specific, prescribed techniques in place of using their own judgment. Donald E. Polkinghorne assembles the case for the return to judgment-based practice for the professions that engage in direct person-to-person interaction with those they serve. Set in the larger context of the technification of society, Polkinghorne draws from Weber, Heidegger, Ihde, Bourdieu, de Certeau, and other philosophers to trace the advancing power of the technological worldview in Western culture and uses Aristotle, Dewey and Gadamer to help make his case that we should be doing things very differently."--BOOK JACKET.
Includes bibliographical references (p. 193-205) and index.
Keywords: Human services -- Philosophy